2014
DOI: 10.1073/pnas.1404596111
|View full text |Cite
|
Sign up to set email alerts
|

Scalable production of mechanically tunable block polymers from sugar

Abstract: Significance In recent years there has been extensive research toward the development of sustainable polymeric materials. However, environmentally benign, bioderived polymers still represent a woefully small fraction of plastics and elastomers on the market today. To displace the widely useful oil-based polymers that currently dominate the industry, a bioderived synthetic polymer must be both cost and performance competitive. In this paper we address this challenge by combining the efficient bioprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
205
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 164 publications
(216 citation statements)
references
References 38 publications
3
205
0
Order By: Relevance
“…Previous work demonstrated that employing HMG-CoA synthase (MvaS) and HMG-CoA reductase (MvaE) from Lactobacillus casei could improve the production of mevalonate (5). Although this meval- onate production strategy was promising, the metabolic burden and genetic instability of plasmid prevented the industrial application (14).…”
Section: Chromosomal Integration Of the Mevalonate Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work demonstrated that employing HMG-CoA synthase (MvaS) and HMG-CoA reductase (MvaE) from Lactobacillus casei could improve the production of mevalonate (5). Although this meval- onate production strategy was promising, the metabolic burden and genetic instability of plasmid prevented the industrial application (14).…”
Section: Chromosomal Integration Of the Mevalonate Pathwaymentioning
confidence: 99%
“…1) (20). Previously, the mevalonate pathway was assembled into a high-copy-number plasmid, pMEV-7, and controlled by the strong synthesized promoter P LlacO1 (5). To achieve comparable production of mevalonate after integrating the mevalonate pathway into the chromosome, we chose a constitutive promoter (M1-93) which is 5-fold stronger than the native P lac promoter.…”
Section: Chromosomal Integration Of the Mevalonate Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Although several PLA-containing block polymers with favorable properties have been reported, the starting materials used for the synthesis of these polymers are either derived from fossil fuels or prohibitively expensive natural products. Recently, Xiong et al developed an efficient biosynthetic route for the production of a branched lactone, β-methyl-δ-valerolactone (βMδVL), which can be transformed into a rubbery polymer with low glass transition temperature [199]. The artificial pathway expands the mevalonate pathway in E. coli, to convert mevalonate to βMδVL (Fig.…”
Section: Pla Copolymers With Improved Propertiesmentioning
confidence: 99%
“…To biosynthesize anhydromevalonolactone, mevalonate was first converted to mevalonyl-CoA using acyl-CoA ligase (SidI) of Aspergillus fumigatus, which was further transformed to anhydromevalonyl-CoA by enoyl-CoA hydratase (SidH) from A. fumigatus, and finally spontaneous cyclization produced anhydromevalonolactone. In the last step, enoate reductases, Oye2 from S. cerevisiae and YqjM mutant from B. subtilis, were used to convert the unsaturated lactone to βMδVL [199]. This bioderived monomer, βMδVL, was converted to a rubbery polymer using controlled polymerization techniques at ambient temperature, and the addition of lactide to poly (β-methyl-δ-valerolactone) midblocks resulted in the first scalable biobased soft polyester block with mechanically tunable properties and a low glass transition temperature of −50 °C [199].…”
Section: Pla Copolymers With Improved Propertiesmentioning
confidence: 99%